New insights into dermatophagy in Himalayan toad Duttaphrynus himalayanus (Günther, 1864) from Pokhara, Nepal - Sapkota, Abhishek; Sapkota, Keshab Raj; Baral, Rishi (Nepalese Journal of Zoology, 2024)
Dermatophagy, the act of consuming shed skin, is documented across various amphibians and reptiles but remains understudied. This study presents the first recorded observation of dermatophagy in Himalayan toad (Duttaphrynus himalayanus) from Pokhara, Nepal. The toad was observed consuming its entire shed skin during a rainstorm, a behavior captured on video over 6 minutes and 18 seconds. We recorded complete consumption of the old skin, unlike previously reported partial dermatophagy in this genus. This observation expands the knowledge of dermatophagy in amphibians.